Wastewater treatment of palm oil mill effluent (POME) by ultrafiltration membrane separation technique coupled with adsorption treatment as pre-treatment - Azmi, Nazatul Shima; Md. Yunos, Khairul Faezah (Elsevier, 2014)
The application of membrane separation technology coupled with adsorption treatment (pre-treatment) can be effective means of treating palm oil mill effluent (POME).The pre-treatment process was done by stirring the raw palm oil mill effluent (POME) with 0.20 g/L of palm kernel shell-based activated carbon (PKS-AC) in 35.94 min with stirring speed 39.82 rpm and able to reduce 71.26% of suspended solid. Ultrafiltration membrane separation was subsequently applied for further treatment of POME. From a random observation on the result, it was found that at pressure 2 bar with 600 rpm speed and pH 8 obtained lower dissolved solid (123.70 mg/L) and turbidity (4.50 NTU) concentration.